(untitled) (Simbiótica. Revista Eletrônica, 2025)
Since the turn of the millennium, video games have expanded and diversified, consolidating a hegemonic position within contemporary pop culture. The gaming audience has also diversified. Today, it is estimated that more than 40% of the global population plays on some type of electronic device. In light of the relevance that games hold in contemporary societies, this thematic dossier aims to bring together works that problematize the relationship between electronic games, culture, and society. The contributions gathered here, originating from different fields of knowledge, address and deepen a set of issues intrinsic to the universe of video games. Thus, this dossier contributes to the strengthening of game studies and serves as an important reference for those dedicated to the investigation of games.